INFLUENCE OF WINTER WHEAT PLANTING TIMES AND FEEDING REGIME ON GRAIN YIELD - O. M. Yusupova (Modern American Journals, 2025)
The article discusses the effects of the sowing date and feeding regime of winter wheat Starshina variety on the irrigation regime of winter wheat and grain yield in saline soils of the Bukhara region. Based on the data obtained, the sowing date of winter wheat Starshina variety was sown from October 10 to October 20, the feeding regime N-250; R-175; K-90 kg/ha was used, and the soil moisture before irrigation was irrigated at 70-80-65% relative to the NDMS. In variant 15, the grain yield of winter wheat was 61.2 c/ha.
Keywords: Winter wheat, salinity, mineral fertilizers, productivity, irrigation standards, feeding.